Pengaruh Fear Of Missing Out (Fomo), Brand Image, Dan Review Content Creator Terhadap Keputusan Pembelian Pada Produk Iphone Di Kalangan Gen Z - Irene Irene; Katherine Vrisilia; Putri Ayu; Holfian Daulat Tambun Saribu; Rintan Br. Saragih (Politeknik Ganesha Medan, 2026)
This study aims to analyze the influence of Fear of Missing Out (FOMO), Brand Image, and Review Content Creator on the Purchase Decision of Iphone products among Generation Z (Gen Z). This research is a quantitative study. Primary data collection was conducted by distributing questionnaires to 118 Gen Z respondents selected using a purposive sampling method. Instrument testing included validity and reliability tests. In the classical assumption test, all variables were transformed into Natural Logarithm (LN) to overcome heteroscedasticity symptoms and ensure the feasibility of the regression model. The data analysis technique used was Multiple Linear Regression Analysis. The results of the study indicate that partially: (1) FOMO has a positive and significant effect on purchase decisions; (2) Brand Image has a positive and significant effect on purchase decisions; and (3) Review Content Creator has a positive and significant effect, while also being the most dominant variable influencing Iphone purchase decisions. Simultaneously, FOMO, Brand Image, and Review Content Creator have a significant effect on purchase decisions with a contribution level (Adjusted R Square) of 76.1%, while the remaining 23.9% is explained by other variables not examined in this study.